(untitled) (Research, Society and Development, 2022)
The objective was to describe, through the process of systematic literature review, the factors that are associated with sports practice and interfere in the quality of life and in the health process. To this end, a systematic review of the qualitative descriptive literature was carried out. Thus, the study was carried out between October and November 2022, with the primary articles being selected from the Latin American and Caribbean Literature in Health Sciences/LILACS and the Virtual Health Library/BVS databases, being used as selection criteria. inclusion: articles available in full, in Portuguese, English and Spanish, within the time frame of 10 years. Furthermore, an inferential analysis technique was adopted, centered on the discussion process, in order to verify the information collected in the primary studies and confront it with the ideas of other authors. As a result, an initial quantity of 284 articles was obtained and after applying the filters, 12 articles were chosen for the construction of this study. Furthermore, quality of life stands out, gaining a more significant impact when associated with the practice of physical exercise, observing its benefits in work environments, social life, improvement of psychiatric conditions, etc. it is concluded that physical exercise presents factors capable of preventing the onset of diseases, chronic non-communicable diseases, healthy aging practices, cardiac events, psychiatric diseases, in addition to helping to develop a life of healthier practices and free of long-term damage.